Participatory shaping of community futures in e‐waste processing hubs: Complexity, conflict and stewarded convergence in a Palestinian context. (5th September 2018) - Davis, John‐Michael; Garb, Yaakov
Abstract: This article describes an unconventional participatory development approach carried out in an informal e‐waste hub in South‐West Hebron, an area that has collected and processed the bulk of Israeli e‐waste for over a decade. Our approach contributes to the critique and recovery of community representation in participatory development and the search for ways to facilitate representative community engagement. Specifically, we describe our use of a novel Delphi‐like method that allowed us to facilitate a broadly endorsed development trajectory within a heterogeneous and conflicted community. We show how the results yielded by this approach diverged from those that were likely to emerge from more facile forms of participation in ways that are important for other similar e‐waste hubs internationally, which face a destructive status quo on the one hand, or the economically ruinous international policies that ban e‐waste trade from "developed" to "developing" countries on the other. Despite real tensions and cleavages within the affected communities, the process described facilitated a shift from deadlocked environmental versus livelihood positions towards building capacity and regulating existing informal e‐waste trades to preserve livelihoods dependent on these.